Efecto de la aplicación de tres niveles de fertilización orgánica en el cultivo de fréjol (Phaseolus vulgaris L.) en la zona de Balzar. - García Sánchez, Kevin Alfredo (2022)
The objective of the research carried out was to evaluate the effect of the application of three levels of organic fertilization in the cultivation of beans (Phaseolus vulgaris L.) in the Balzar area. For this purpose, the trial was established at the EnGar farm located at km 14.3 of the Balzar – El Empalme road. Four treatments were evaluated: T1: 20 L/ha of biol; T2: 40 L/ha of biol; T3: 60 L/ha of biol and T4: Without fertilization, under a randomized complete block design with five repetitions. Data on plant height, number of nodules per plant, stem diameter, number of pods per plant, grains per pod, weight of 100 grains, yield per hectare were recorded and complemented with the respective economic analysis. The results obtained showed that T3: 60 L/ha of biol showed better results in the development of the crop, showing taller plants, with more nodules per plant, which in turn presented stems with a larger diameter, reflecting a greater benefit in these indicators due to said treatment. Yield indicators were significantly enhanced when applying T3: 60 L/ha of biol, which, due to a higher production of pods and grains per pod, which, in synergy with a higher weight of grains, reached a higher level of yield per hectare. (839.29 kg). In addition, the economic benefit was greater when the crop was fertilized with the application of T3: 60 L/ha of biol, with 54.37% being the only treatment that presented positive profitability.